Analisis Kepatuhan Prosedur Eksekusi Jaminan Gadai Emas dalam Perspektif Hukum Perdata : Study Kasus Sita Jaminan Gadai Pada Putusan Ma No.738/Pdt.G/2023/Pn Mdn (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This research examines compliance with gold pawn guarantee execution procedures from a civil law perspective, using a case study of Medan District Court Decision Number 738/Pdt.G/2023/PN Mdn. The background to this research stems from the growing practice of gold pawning in society as a solution for quick cash needs, but it often raises legal issues related to the execution process of the pawned goods. The issues raised in this paper are the procedures for executing gold pawn guarantees according to applicable law and whether PT. Gadai Mas Sumut's actions in this case comply with legal provisions. This research method uses a normative juridical approach by examining Articles 1150-1160 of the Civil Code, the Consumer Protection Law, and PMK Number 122 of 2023. The analysis shows that, normatively, creditors have the right to execute pawned goods if the debtor defaults. However, execution must be carried out in accordance with legal procedures, the principle of good faith, and transparency, including through a public or voluntary auction. In the case of PT. In the case of the North Sumatra Gold Pawn, the execution was carried out without adequate notification and without evidence of an official auction, thus being deemed to have failed to meet the principle of legal compliance. Therefore, this article concludes that gold pawn execution practices must be based on the principles of legal certainty and debtor protection to prevent similar losses and disputes in the future.